Can the Hydroxyapatite-Coated Skin-Penetrating Abutment for Bone Conduction Hearing Implants Integrate with the Surrounding Skin? - van Hoof, Marc; Wigren, Stina; Duimel, Hans; Savelkoul, Paul H. M.; Flynn, Mark; Stokroos, Robert Jan (Frontiers in Surgery, 2015)
Introduction Percutaneous implants, such as bone conduction hearing implants, suffer from complications that include inflammation of the surrounding skin. A sealed skin–abutment interface can prevent the ingress of bacteria, which should reduce the occurrence of peri-abutment dermatitis. It was hypothesized that a hydroxyapatite (HA)-coated abutment in conjunction with soft tissue preservation surgery should enable integration with the adjacent skin. Previous research has confirmed that integration is never achieved with as-machined titanium abutments. Here, we investigate, in vivo, if skin integration is achievable in patients using a HA-coated abutment. Materials and methods One titanium abutment (control) and one HA-coated abutment (case) together with the surrounding skin were surgically retrieved from two patients who had a medical indication for this procedure. Histological sections of the skin were investigated using light microscopy. The abutment was qualitatively analyzed using scanning electron microscopy. Results The titanium abutment only had a partial and thin layer of attached amorphous biological material. The HA-coated abutment was almost fully covered by a pronounced thick layer of organized skin, composed of different interconnected structural layers. Conclusion Proof-of-principle evidence that the HA-coated abutment can achieve integration with the surrounding skin was presented for the first time.